(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
The article presents the list of wild growing fruit and berry plants of Armenia, made up in accordance with existing literature and own investigations. There are 17 families and 59 species of fruit and berry plants, growing in Armenia. The table shows existing fruit-consumption levels (widely consumed and sold in markets, locally used by population for personal needs, potentially usable), the usage of the plants in scientific and folk medicine and representation in the Red Book of Armenia is marked in the table as well.